Features of learning motivation in the conditions of coronavirus pandemic (COVID-19) - Oleg Pursky; Anna Selivanova; Iryna Buchatska; Tatiana Dubovyk; Tatiana Tomashevska; Hanna Danylchuk (Academy of Cognitive and Natural Sciences, 2021)
This article has been retracted. Please see: Retraction of published article due to the author's proposal - 6 August 2022   Maintaining motivation plays a special role during the introduction of distance learning in connection with the coronavirus epidemic. To analyze the features of motivation in different learning conditions, a graphic model of the student motivation has been presented. The effectiveness of the model was tested in both offline and online learning. The study showed that the influence of the main motivational components in the conditions of offline learning varies from primary school to higher education. The youngest students are best motivated to learn in a situation where the inner desire to learn something new is constantly supported by external stimulation. In primary school, the motivating influence of teachers and parents gradually decreases, but both the negative and positive influence of an important environment (friends, reference adults) increases. Adolescents have clearly defined learning goals. The impact of online learning on this category of students is quite controversial. The study has found mixed trends -- both an increase in motivation for learning and a sharp decrease. The first group is quietly moving to online learning, making extensive use of the Internet. The second either completely lose motivation to learn or shows unstable motivation, which either sharply decreases, then just as sharply increases.